Notes sur la géologie et la paleontology du Miocène de Lisbonne. XXII - Une Espèce nouvelle Pokornyella Lusitanica (Ostrocoda), dans le Miocène Inférieur du bassin du Tage - Nascimento, A. (2008)
A new species, Pokornyella lusitanica (Ostracoda), from the Lower Miocene (Aquitanian) of the Lisbon area, is described. Some palaeoecological data are presented.